Factors Affecting Public Speaking Success among BSOA Students as the Basis for Instructional Material - Ashley Jane B. Relativo; Vernadith T. Vargas; Natasha Mae S. Llanes; Alyssa Florese De Loyola–Lagatic (The Indonesian Institute of Science and Technology Research, 2026)
This study was conducted to determine the factors affecting public speaking success among Bachelor of Science in Office Administration (BSOA) students at Camarines Sur Polytechnic Colleges. The research explores how psychological, linguistic, social, and technological factors affect students' abilities to communicate effectively. Data was gathered from 244 respondents and analyzed using quantitative methods, including weighted mean, ranking scale, and chi-square tests. The findings reveal a significant relationship between these factors and public speaking performance. Psychological factors indicate that confidence and mental readiness significantly affect a student's ability to speak in public. Linguistic factors highlight the importance of clear and effective language skills. Social factors suggest that interaction and engagement with peers enhance speaking abilities. Technological factors show that familiarity with digital tools and platforms positively influences performance. These results emphasize the need for a comprehensive approach to enhance students' public speaking skills. An intervention program is proposed to address these factors, aiming to boost confidence, improve language proficiency, encourage social interaction, and enhance technological competence. This study provides valuable insights for educators and policymakers, emphasizing the importance of tailored strategies to foster effective communication. By addressing these key areas, students can develop the skills necessary for academic and professional success, contributing to their overall development in a dynamic and competitive environment.